Hubungan Paparan Merkuri (Hg) Dengan Kejadian Gangguan Fungsi HatiPada Pekerja Tambang Emas di Wonogiri - Dewanti, Nikie Astorina Yunita; Setiani, Onny; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background: Traditional gold mining activities that using WOA/ amalgamation can cause Hg emissions to the environment. The emissions could raise mercury poisoning in the environment and human. Liver as a major part of the metabolism and accumulation of Hg in the human body, so that Hg could lead to liver damage. In the previous research, Hg exposure in male rats caused hepatotoxicosis. Average blood mercury levels of workers was 53.5 μg/m3. Objective: To determine the association between mercury (Hg) exposure and theoccurance of liver dysfunction on gold mine workers at Jendi Village, sub-district Selogiri, Wonogiri District. Methods: It was a cross-sectional study, total sample were 41 workers. The data obtained from the results of laboratory tests of blood samples and the results of the interview respondents.Data would be analyzed using biavariate and multivariate statstic test. Results:There was 41.16% of respondents were miners, processors as well as grates, the average of working period was 10 years, work duration 6 hours a  day and 6 days a week. 97.56% of respondents have blood mercury levels above normal (U.S. EPA: 5.8 ppb). Elevated levels of SGOT experienced by 24.4% of respondents , SGPT 17.1% of  respondents and ALP 58.8% of  respondents or as much as 68.3% of respondents having liver disfunction. There was no difference incidence of liver dysfunction seen from the type of work (p value = 0.459), There was no assossiation between  work duration, work period and blood mercury  levels with the incidence of liver disfunction in workers (p value = 0.148; 0.408 and 0.608). There was a relationship between blood mercury levels with SGPT as an indicator of liver dysfunction (p value = 0.042) Conclusion: Overall, the data did not provide strong evidence that mercury exposure associated with incidence of liver disfunction.   Keywords: mercury exposure, liver disfunction, SGOT, SGPT, ALP